The Association of Sleep Disordered Breathing with Heart Failure and Other Cardiovascular Conditions - Elizabeth Stopford; Karthik Ravi; Vikrant Nayar (Cardiology Research and Practice)
An abundance of evidence exists in support of primary and secondary prevention for tackling the scourge of cardiovascular disease. Despite our wealth of knowledge, certain deficiencies still remain. One such example is the association between sleep disordered breathing (SDB) and cardiovascular disease. A clear body of evidence exists to link these two disease entities (independent of other factors such as obesity and smoking), yet our awareness of this association and its clinical implication does not match that of other established cardiovascular risk factors. Here, we outline the available evidence linking SDB and cardiovascular disease as well as discussing the potential consequences and management in the cardiovascular disease population.